Pragmatism in Islamic Higher Education: Navigating Social Trends and Academic Orientations - Emawati Emawati; Nurkhamid Nurkhamid (Universitas Nurul Jadid, 2025)
This study describes the phenomenon of pragmatic lifestyle orientation among students at the Faculty of Ushuluddin Adab and Humanities (FUADAH) UIN Salatiga. A pragmatic lifestyle is the tendency of students to pursue instant results, such as high grades and quick completion of tasks, driven by the pressures of a results-oriented system. Research questions: how did this pragmatic orientation come about, what are the driving factors, and how does it impact students' learning strategies and academic achievements? The research aims to uncover the manifestations of this pragmatic lifestyle, distinguishing it from the general philosophical study of pragmatism. Using a qualitative method with an Islamic anthropological perspective, the researcher analyzed students' behavioral adaptation. The study subjects were 19 students from the AFI Study Program. We analyzed data through interviews, participatory observations, and a literature review. The results show that students tend to adopt lifestyles that prioritize efficiency, practicality, and tangible results. The main driving factors are the competitive environment and technological advancements. As many as 100% of students admit to using technology (such as AI and Google) to speed up tasks. The chosen learning strategies focused on effectiveness and efficiency (74%), and this reportedly affected their GPA (79%). This research is essential because it provides practical insights for institutions and lecturers to design teaching strategies that strike a balance between practical orientation and in-depth intellectual exploration. This study aims to support student success without sacrificing essential academic values such as critical thinking and integrity.